2021
DOI: 10.1155/2021/6635245
|View full text |Cite
|
Sign up to set email alerts
|

Study on Permeability of Deep‐Buried Sandstone under Triaxial Cyclic Loads

Abstract: The triaxial cyclic loading and unloading test was carried out on a TAW-2000 rock mechanics to study the permeability characteristics of deep-buried sandstone. This paper analyzed the evolution laws of permeability, elastic modulus, rock damage, dissipated energy, and acoustic emission events of sandstone under different confining pressures. It also introduced the concept of relative strain and further discussed the relationship between relative strain and permeability. The test results showed that the permeab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Similar experiments on sandstone rocks reveal a strong correlation between the strain accumulated in each cycle and the resulting change of permeability and after 30 cycles, the permeability change becomes negligible as the strain stabilises [91]. Those irreversible changes in permeability are shown to be more pronounced for reservoirs of low permeability [92,93,94,95,96]. Low-and high-frequency oscillation-based creep experiments of pore pressure in sandstones concluded that even a significant monotonic increase in pore pressure has a minor effect on the mechanical properties of the rock [97].…”
Section: Cyclic Pore Fluid Injectionmentioning
confidence: 55%
“…Similar experiments on sandstone rocks reveal a strong correlation between the strain accumulated in each cycle and the resulting change of permeability and after 30 cycles, the permeability change becomes negligible as the strain stabilises [91]. Those irreversible changes in permeability are shown to be more pronounced for reservoirs of low permeability [92,93,94,95,96]. Low-and high-frequency oscillation-based creep experiments of pore pressure in sandstones concluded that even a significant monotonic increase in pore pressure has a minor effect on the mechanical properties of the rock [97].…”
Section: Cyclic Pore Fluid Injectionmentioning
confidence: 55%
“…Most of them start from the triaxial unloading test to study the crack evolution and failure mechanism, mechanical parameter damage degradation effect, and strength characteristics of various rocks during unloading [3][4][5][6]. Considering the influence of unloading rate on rock failure mode, triaxial unloading tests under different unloading rates were designed and carried out to analyze the failure characteristics of rock [7][8][9][10]. On this basis, many scholars intervened in the influence of various unloading paths and studied the energy evolution characteristics of rock in triaxial unloading failure processes from macro and meso perspectives [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…With the continuous development of human beings to the depth in the process of underground engineering development and construction, especially the mining depth of underground mineral resources has reached more than 1000 meters, the engineering problems encountered are becoming more and more complex and have great particularity compared with surface engineering. The seepage and stress caused by engineering excavation are the key factors affecting coal mine safety production, and the water gushing caused by high underground water pressure is the potential danger of mining activities [1][2][3][4]. Among them, the serious deformation and damage of roadway (tunnel), especially the prominent phenomenon of floor heave is a more common engineering problem.…”
Section: Introductionmentioning
confidence: 99%